2016
DOI: 10.1016/j.jacc.2016.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Cerebrovascular Events in Patients With Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement

Abstract: Female sex, chronic kidney disease, enrollment date, and new-onset atrial fibrillation were predictors of CVE post-TAVR. This study provides effect estimates to identify high-risk TAVR patients for early CVE, providing possible guidance for tailored preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(83 citation statements)
references
References 98 publications
9
69
1
4
Order By: Relevance
“…Post‐hoc data from the PARTNER trial and other observational and meta‐analytical studies have shown new‐onset AF to be associated with greater risk for cerebrovascular events at 30 days. However, despite the anticipated adverse effects of AF, we did not observe statistically significant differences in 30‐day risk of outcomes compared with patients in sinus rhythm in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…Post‐hoc data from the PARTNER trial and other observational and meta‐analytical studies have shown new‐onset AF to be associated with greater risk for cerebrovascular events at 30 days. However, despite the anticipated adverse effects of AF, we did not observe statistically significant differences in 30‐day risk of outcomes compared with patients in sinus rhythm in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…In the US CoreValve studies, stroke occurred in 8.4% of patients at 1 year, and nearly half of the events occurred in the first 10 days after TAVR . In a meta‐analysis of >72,000 patients from 64 studies, 2,385 cerebrovascular events occurred within 30‐days . Across the study centers, the incidence ranged from 1% to 11%, with a median incidence of 4%.…”
Section: Introductionmentioning
confidence: 99%
“…Defined according to VARC‐2 as a composite of all‐cause mortality, non‐fatal stroke, non‐fatal myocardial infarction, acute kidney injury, and pacemaker implantation within 30 days (±7) after TAVI …”
Section: Resultsmentioning
confidence: 99%
“…Post‐dilatation during the TAVI procedure may have a negative effect on prosthesis durability and increase the risk of cerebrovascular events . As such, its evasion is desirable.…”
Section: Discussionmentioning
confidence: 99%